Analysis of discounted payback in residencial rainwater collection systems in the State of Santa Catarina - Silva, Carlos Eduardo da (2018)
This work aims at the central analysis of the time of recovery of investment in rainwater harvesting systems for use in single family homes in the State of Santa Catarina. As a secondary objective it was installed as a construction of two PHP and HTML analysis softwares (SILVA, 2017a, 2017b): (1) Sizing of Water and Rain Reservoirs and (2) Calculation of Discounted Payback. Residences located in five cities of the State were analyzed with the application of a sensitivity analysis to verify the Discounted Payback with different levels of rainfall, varying the number of inhabitants between three and five people, as mixed with several roof packages (in order to investigate several real estate). It has been found that it is an economically viable investment mainly for families who already have a large water consumption in their largest number of residents and in cities where their cost is high. Cities with a higher rainfall index are also more favored because they require an infrastructure that requires a lower initial investment.